The knowledge, attitude and behavior of ICU nurses regarding ICU-acquired weakness: a cross-sectional survey - Mingfeng Zhao; Anyun Qiu; Zhijing Zhang; Fang Pan; Yongxia Gao (BMC, 2024)
Abstract Background Intensive care unit-acquired weakness (ICU-AW) is very common in ICU patients. It is important to understand the status quo of knowledge, attitude and behavior of ICU nurses about ICU-AW. This survey aimed to investigate the knowledge, attitude and behavior of ICU nurses about ICU-AW, to provide useful implications for clinical care. Methods ICU nurses from two tertiary hospitals in China from October 10 to November 15, 2023 were included. The ICU-AW knowledge, attitude and behavior questionnaire of ICU nurses with 31 items were used for survey. SPSS24.0 statistical software was used for data analysis. Results A total of 364 ICU nurses were included for survey. The ICU-AW knowledge of ICU nurses was 21.96 ± 5.72 (< 50% of the total knowledge score), the ICU-AW attitude of ICU nurses was 30.24 ± 5.05(< 75% of the total attitude score), the ICU-AW behavior of ICU nurses was 26.77 ± 5.81(< 75% of the total behavior score), the total score was 79.21 ± 12.69(< 75% of the total score). Nurses' ICU-AW knowledge, attitude and behavior were all correlated (all P < 0.05). Multiple linear regression analyses indicated that age, years of ICU work experience, professional ranks and titles, had received the training about the ICU-AW were the influencing factors of knowledge, attitude and behavior of ICU nurses about ICU-AW (all P < 0.05). Conclusions The knowledge, attitude and behavior of ICU nurses' ICU-AW needs to be improved, and there are many influencing factors. Hospital nursing administrators should strengthen the training of nurses' ICU-AW knowledge and improve the cognitive and practical ability of ICU nurses on ICU-AW, so as to reduce the occurrence of ICU-AW.